Robot vision through cloud for embedded device - Wong, Jeffrey Haw Yin (2020)
In this project, an application of robot vision through the cloud will be developed as Artificial Intelligence had become the trend of the world. It is surrounded the human nowadays. When heard about AI, the image that comes into the mind of most of the people are a robot. In 2018, Asia was the world’s largest industrial robot market over the world. Two out of three robots that are newly deployed in 2018 were installed in Asia. It shows that there is a high demand for robotic in Asia over the world. The installation rate of robots rose by 23% per year from the year 2013 to the year 2018. Human is using their eye to increases the efficiency of doing their jobs. It is also same as the robot. They are also needed to have their eye increases their efficiency in doing their jobs. At the end of the project, a path finding robot will be developed.